Genome-Wide Identification of WRKY Genes and Their Responses to Chilling Stress in Kandelia obovata - Du, Zhaokui; You, Shixian; Zhao, Xin; Xiong, Lihu; Li, Junmin (Frontiers in Genetics, 2022)
Background: Kandelia obovata, a dominant mangrove species, is widely distributed in tropical and subtropical areas. Low temperature is the major abiotic stress that seriously limits mangrove trees. WRKY transcription factors (TFs) play vital roles in responses to biotic and abiotic stresses. However, genome-wide analysis of WRKY genes in K. obovata and their responses to cold stress have not been reported. Methods: Bioinformatic analysis was used to identify and characterize the K. obovata WRKY (KoWRKY) gene family. Results: Sixty-four KoWRKYs were identified; these proteins belonged to three groups (I, II, III) according to their conserved WRKY domains and zinc-finger structure. These KoWRKYs were unevenly distributed across all 18 K. obovata chromosomes. Many orthologous WRKY gene pairs were identified between Arabidopsis thaliana and K. obovata, showing high synteny between the two genomes. Segmental duplication events were found to be the major force driving the expansion for the KoWRKY gene family. Most of the KoWRKY genes contained several kinds of hormone- and stress-responsive cis-elements in their promoter. Expression patterns derived from the RNA-seq and qRT–PCR analyses revealed that 9 KoWRKYs were significantly upregulated during cold acclimation in the leaves. KEGG pathway enrichment analysis showed that the target genes of KoWRKYs were mainly involved in 11 pathways, and coexpression network analysis showed that 315 coexpressed pairs (KoWRKYs and mRNAs) were positively correlated. Conclusions: Sixty-four KoWRKYs from the K. obovata genome were identified, 9 of which exhibited cold stress-induced expression patterns. These genes represent candidates for future functional analysis of KoWRKYs involved in low temperature-related signaling pathways in K. obovata. Our results provide a basis for further analysis of KoWRKY genes to determine their functions and molecular mechanisms in K. obovata in response to cold stress.